Solutions for Some Elliptic Problems with Double Resonance - Qian, Aixia (Communications in Mathematics and Applications, 2014)
In this paper, we prove the existence results and multiplicity results of nontrivial solutions for some elliptic problems with double resonance by using Morse theory.